2017
DOI: 10.1159/000477126
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Amyotrophic Lateral Sclerosis in the Republic of Cyprus: A 25-Year Retrospective Study

Abstract: Introduction: Amyotrophic lateral sclerosis (ALS) is a rare, rapidly progressive neurodegenerative disease. Despite wide variability in the incidence and prevalence of ALS, there is evidence of positive temporal trends and an increase in incidence with age. The aim of this study was to conduct a detailed epidemiological investigation of ALS in Cyprus. Methods: All registered Cypriot ALS patients in the Republic of Cyprus from January 1985 until December 2014 were included. Socio-demographic information was ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
4
9
0
Order By: Relevance
“…ALS patients’ clinical characteristics, as a total and stratified by gender, are presented in Table 1. As previously reported[10], there was a male predominance with a gender ratio of 1.45 M:F (106/73), disease onset was at a mean age of 58.6±10.9 years, diagnosis was at a mean age of 59.8±10.6, and only 4% (n = 7) of our sample had a family history of ALS. Clinical characteristics did not differ between gender categories (Table 1).…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…ALS patients’ clinical characteristics, as a total and stratified by gender, are presented in Table 1. As previously reported[10], there was a male predominance with a gender ratio of 1.45 M:F (106/73), disease onset was at a mean age of 58.6±10.9 years, diagnosis was at a mean age of 59.8±10.6, and only 4% (n = 7) of our sample had a family history of ALS. Clinical characteristics did not differ between gender categories (Table 1).…”
Section: Resultssupporting
confidence: 72%
“…This study is a retrospective clinical investigation of previously identified[10] ALS patients seen at the Cyprus Institute of Neurology and Genetics (CING) between 1 January 1985 and 31 July 2015. Recruitment details of patients are outlined elsewhere[10].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations